Impact of venous thromboembolism on incidence of arterial thromboembolism: an analysis of German outpatient claims data - Keller, Karsten; Kohring, Claudia; Farmakis, Ioannis T.; Valerio, Luca; Barco, Stefano; Bätzing, Jörg; Akmatov, Manas K.; Konstantinides, Stavros; Münzel, Thomas; Hobohm, Lukas; Holstiege, Jakob (Thrombosis research, 2023)
Background - Venous thromboembolism (VTE) and arterial thromboembolism (ATE) are considered as two separate disease-entities. In recent years, studies have reported clear associations between VTE and atherosclerosis. We aimed to evaluate the long-term risk of ATE in VTE patients in comparison to controls without VTE. - Methods - Nationwide outpatient claims data of all inhabitants with statutory health insurance in Germany were used for secondary data analysis between the years 2011 and 2020. Patients treated in 2013 were stratified by VTE event, and groups were 1:2-matched by age and sex. The hazard for an ATE event in a 5-year follow-up period between patients with and without VTE was calculated with multivariable Cox regression adjusted for age, sex, cardiovascular risk factors, and comorbidities. - Results - Of 69,699,277 individuals treated in the year 2013 by German physicians in outpatient care, in total 686,382 individuals (age 59.8 ± 17.5 years, 65.4 % females) were included comprising 228,794 patients with VTE and 457,588 controls without VTE. VTE patients more often had cardiovascular risk factors (81.6 % vs. 62.2 %) and traditional VTE risk factors. The occurrence of ATE events during follow-up was 1.8 %-points higher in VTE patients in comparison to the controls (9.7 % vs. 7.9 %). VTE events were independently associated with increased occurrence of ATE events within follow-up (HRadjusted 1.19 [99%CI 1.16-1.23], p < 0.0001). - Conclusions - Patients with a VTE event have an increased long-term risk for subsequent arterial cardiovascular events. Large prospective cohorts are needed to identify patient subgroups with a very high ATE risk after VTE.
Gesehen am 04.08.2023